DEVELOPMENT OF VIRTUAL REALITY APPLICATION FOR DESKTOP COMPUTER ASSEMBLY - Sapta, Andy; Mansur, Hamsi; Hakim, Abdul; Agung, Muhammad; Dalu, Zaudah Cyly Arrum (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: Both hardware and software technologies offer their advantages in helping to facili- tate student learning activities. Virtual reality technology allows users to interact directly with  the virtual reality environment, giving the effect of a pleasant learning sensation because it pro- vides direct experience for students to actively do desktop computer assembly practicum inde- pendently and guided. This research is R & D (Research and Development), which aims to pro- duce a product as a desktop computer assembly virtual reality learning application. This re- search procedure adapts the Lee & Owens development model. The subjects of this research  were students at the Open University, Makassar State University, and Lambung Mangkurat  University. The results showed that using Virtual Reality in desktop computer assembly can  provide extraordinary experiences to users, bridging the gap between the real and virtual worlds.  This is achieved through specially designed hardware to create a virtual environment that re- sembles the actual reality or even creates an entirely new reality.  Keywords: desktop computer; assembly; virtual reality     Abstrak: Teknologi perangkat keras (hardware) maupun lunak (software) menawarkan  keunggulannya dalam membantu memfasilitasi aktivitas belajar dan pembelajaran ma- hasiswa. Teknologi virtual reality memiliki kemampuan bagi penggunanya untuk dapat  melakukan interaksi langsung dengan lingkungan realitas maya, memberi efek sensasi  pembelajaran yang menyenangkan karena memberikan pengalaman langsung bagi ma- hasiswa untuk aktif melakukan pratikum perakitan computer desktop secara mandiri  maupun terbimbing. Penelitian ini adalah R & D (Research and Development) yang ber- tujuan untuk menghasilkan suatu produk yaitu berupa aplikasi pembelajaran virtual real- ity perakitan computer desktop. Prosedur penelitian ini mengadaptasi model pengem- bangan Lee & Owens. Subjek penelitian ini adalah mahasiswa pada Universitas Ter- buka,  Universitas  Negeri  Makassar,  dan  Unibversitas  Lambung  Mangkurat.  Hasil  penelitian diperoleh bahwa penggunaan Virtual Reality dalam perakitan computer desk- top mampu memberikan pengalaman luar biasa kepada pengguna, menjembatani jurang  antara dunia nyata dan dunia maya. Hal ini dicapai melalui penggunaan perangkat keras  yang dirancang khusus untuk menciptakan lingkungan virtual yang menyerupai realitas  sebenarnya atau bahkan menciptakan realitas yang sama sekali baru. Kata kunci: computer desktop; perakitan; virtual reality